Promoting Family Engagement in the ICU: Experience From a National Collaborative of 63 ICUs*. Issue 12 (December 2019) - Kleinpell, Ruth; Zimmerman, Jerry; Vermoch, Kathleen L.; Harmon, Lori A.; Vondracek, Hugh; Hamilton, Rebekah; Hanson, Bruce; Hwang, David Y.
Abstract : Objectives: As part of an improvement program targeting ICU, a national collaborative was launched to help hospitals implement patient- and family-centered care engagement initiatives. Design: Ten-month quality improvement collaborative. Setting: Guided by a national patient and family advisory group, participating teams implemented an individual project including open visitation; integrating families on rounds; establishing a patient and family advisory committee; using patient and family diaries, among others. Subjects: Sixty-three adult and PICU teams from both academic and community hospitals in 34 states participated. Interventions: Monthly team calls, quarterly webinars, newsletters, an online eCommunity, and team reporting assignments were used to facilitate project implementation. Measurements and Main Results: The Family Satisfaction with Care in the ICU 24 was used to assess family satisfaction. Clinician perceptions were assessed with the Institute for Patient- and Family-Centered Care Self-Assessment Inventory. Thematic analysis was used to explore narrative data captured from team reports of project barriers, facilitators, and the experience of participating in the collaborative. A total of 2, 530 family member and 3, 999 clinician surveys were completed. Postimplementation, family members reported statistically significant increases in overall family satisfaction, satisfaction with decision-making, and satisfaction with quality of care (Family Satisfaction with Care in the ICU mean score change range 0.83–1.24; p ⩽ 0.027). Clinicians reported that opportunities for families to participate as members of the care team increased. Major barriers included lack of buy-in and ability to promote change in the clinical setting, managing the workload of implementation, and funding to support initiatives. Conclusions: A national collaborative format was useful to assist ICU teams to implement patient- and family-engagement initiatives. Enlisting stakeholder support, engaging unit-based champions, and highlighting benefits of family engagement can help ICU teams to promote family member involvement and engagement. Abstract : Supplemental Digital Content is available in the text.